STRATEGI BADAN PENDAPATAN DAERAH(BAPENDA) DALAM MENINGKATKAN PENDAPATAN ASLI DAERAH (PAD) MELALUI PEMBAYARAN PAJAK HOTEL DI KABUPATEN SIKKA - Erna Sari; Andreas Rengga; Kristina Reinildis Aek (sekolah Tinggi Ilmu Ekonomi Dharmaputra Semarang, 2025)
The Sikka Regency Regional Revenue Agency (Bapenda) has a strategic role in managing Regional Original Income (PAD), which includes various types of regional taxes, one of which is hotel tax. Hotel tax makes a significant contribution to increasing PAD, but there are various challenges in collecting it, such as erratic income fluctuations and inaccuracies in tax reporting by taxpayers. This research aims to analyze the strategies implemented by the Sikka Regency Bapenda in increasing hotel tax payments and identify the obstacles faced in implementing the self-assessment system. The research method used is qualitative with data collection techniques through interviews, observation and documentation studies. The research results show that Bapenda has implemented various strategic steps, such as socializing taxes to the public, carrying out sampling tests to ensure taxpayer compliance, installing online transaction recording devices (M-Pos), and implementing a QRIS-based tax payment system to make transactions easier. Apart from that, Bapenda also establishes partnerships with related agencies, such as Bank NTT, Bank BNI, Civil Service Police Unit (POLPP), and the Prosecutor's Office, to strengthen supervision and enforcement of tax laws. Even though these efforts have shown positive results, the main challenge remains the low level of awareness and honesty of taxpayers in reporting, which requires more intensive supervision and ongoing education.